2017
DOI: 10.1016/j.mce.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A single cell level measurement of StAR expression and activity in adrenal cells

Abstract: The Steroidogenic acute regulatory protein (StAR) directs mitochondrial cholesterol uptake through a C-terminal cholesterol binding domain (CBD) and a 62 amino acid N-terminal regulatory domain (NTD) that contains an import sequence and conserved sites for inner membrane metalloproteases. Deletion of the NTD prevents mitochondrial import while maintaining steroidogenesis but with compromised cholesterol homeostasis. The rapid StAR-mediated cholesterol transfer in adrenal cells depends on concerted mRNA transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…The 3D spatial distribution of StAR loci, mRNA, and protein which is central to the sm-FISH assessment of gene expression was best seen in MA-10 cells. Thus, StAR protein and mRNA after 3 h of stimulation showed very characteristic 3D organizations ( 38 ) (Figure 4 B). The StAR protein in these mitochondria is located in the matrix and is inactive in promoting cholesterol transfer to Cyp11a1.…”
Section: Resultsmentioning
confidence: 98%
“…The 3D spatial distribution of StAR loci, mRNA, and protein which is central to the sm-FISH assessment of gene expression was best seen in MA-10 cells. Thus, StAR protein and mRNA after 3 h of stimulation showed very characteristic 3D organizations ( 38 ) (Figure 4 B). The StAR protein in these mitochondria is located in the matrix and is inactive in promoting cholesterol transfer to Cyp11a1.…”
Section: Resultsmentioning
confidence: 98%
“…34 On the other hand, SIKs also transcriptionally regulate the Na + ,K + -ATPase, either by directly inhibiting the entry of CRTC into the nucleus to transcript ATP1B1 gene, which encodes a Na + , K + -ATPase subunit, 2 or by indirectly repressing the hormonesinduced Na + ,K + -ATPase expression, 74 via an increased CYP11A and StAR mRNA levels to promote the adrenocorticotropic hormone production. 55,[75][76][77] Other downstream signaling pathways TGFβ-Smad pathway. In normal epithelial cells, TGFβ-Smad signaling pathway is considered to play an anti-cancer role by inducing cell cycle arrest and apoptosis.…”
Section: Sik Downstream Substratesmentioning
confidence: 99%
“…115 Subsequent studies demonstrated that SIK1 repressed the efficient operation of the CREB transcription activation complex, thereby inhibiting the CREdriven transcription of the CYP11A gene and the StAR gene in Y1 cells. 55,[75][76][77] Du et al 116 found that, similar to SIK1, SIK2 can also repress the expression of lipogenic genes (FAS, ACC2 and SCD1), and this effect can be reversed by depleting SREBP1. In addition, SIK2 promotes fatty acid synthesis by upregulating SREBP1c expression, thus promoting the transcription of Fasn in ovarian cancer cells.…”
Section: Sik Functions In Glucose Uptakementioning
confidence: 99%
See 2 more Smart Citations